Radiometry on Argo Floats: From the Multispectral State-of-the-Art on the Step to Hyperspectral Technology - Jemai, Ahlem; Wollschläger, Jochen; Voß, Daniela; Zielinski, Oliver (Frontiers in Marine Science, 2021)
Over the past two decades, robotic drift bodies such Argo floats have revolutionized the capability for operational autonomous measurement of the oceans. Recently, Biogeochemical Argo floats (BGC-Argo floats) have measured optical and biogeochemical parameters within the upper 2000 m on a global scale. Among these parameters are measurements of the underwater light field, from which apparent optical properties can be derived. Presently, multispectral observations at three wavelengths (with 10-20 nm bandwidths) in the blue-green range of the spectrum plus the Photosynthetically Available Radiation (PAR; integrated radiation between 400 and 700 nm), are generally available using this platform. This article reviews the studies dealing with these radiometric observations and presents the current state-of-the-art of Argo radiometry. It focuses on the successful portability of radiometer onboard Argo float platforms and covers applications of the obtained data in bio-optical modelling and ocean color remote sensing. As this existing combination are already generating high-quality datasets, the BGC-Argo program must now investigate the potential to incorporate hyperspectral technology. The advent of such combination and the subsequent development of new algorithms that exploit hyperspectral information will open new opportunities for bio-optical long-term studies of global ocean process but present also new challenges related to the increased amount of data.